The clinico-epidemiological profile and safety and effectiveness of polygeline in Indian patients presenting with hypovolemia: results from a prospective, multicentre, single-arm and open-label post-marketing observational study - Shah, Sanjay; Singh, Ajai; Krishnamurty; Vyawahare, Sarang; Khandale, Vijay; Chowan, Kiran; Bhole, Milind; Acharya, Shivani; Rane, Rhutuja (International Surgery Journal, 2026)
Background: Severe trauma and acute fluid loss are major causes of hypovolemia, linked to high morbidity and mortality if untreated. Intravenous fluid resuscitation, including plasma volume expanders (PVEs), is essential for restoring intravascular volume and perfusion. Polygeline, a gelatine-based colloid, is widely used; however, Indian real-world safety and effectiveness data remain limited. Objectives were to describe the demographic and clinico-epidemiological profile of Indian patients with hypovolemia and to evaluate the effectiveness and safety of Polygeline 3.5% intravenous infusion in routine clinical practice. Methods: This prospective, multicentre, open-label, post-marketing observational study enrolled 154 patients aged 18-65 years who received polygeline 3.5% IV infusion. Demographic and clinical characteristics were documented. Effectiveness was assessed by changes in hemodynamic parameters, urine output, respiratory rate, metabolic markers, pallor, and skin condition over 24 hours. Safety and tolerability were monitored throughout the study. Results: Hypovolemia was equally attributed to traumatic and non-traumatic causes. Among traumatic cases, 46% were classified as class II hypovolemia and 4.7% as class III, while non-traumatic cases showed fewer moderate to severe presentations. Over 24 hours, significant improvements were observed in hemodynamic parameters: mean systolic blood pressure increased from 99.99 to 119.11 mmHg, diastolic pressure from 61.68 to 74.43 mmHg, pulse rate declined from 104.60 to 85.53 bpm, respiratory rate from 21.57 to 18.82 breaths/min, and urine output increased from 21.08 to 218.90 mL (p<0.0001). One non-serious adverse drug reaction (0.6%) was reported and resolved without intervention. Conclusions: Polygeline 3.5% IV infusion demonstrated effective hemodynamic stabilization with a favourable safety profile in patients with hypovolemia of traumatic and non-traumatic origin.